Accuracy and finish during wire electric discharge machining of metal matrix composites for different reinforcement size and machining conditions - Pramanik, A.; Islam, M.; Boswell, B.; Basak, A.; Dong, Yu; Littlefair, G. (SAGE, 2016)
Electric discharge machining has been established as an effective alternative process to conventional material removal processes for machining reinforced metal matrix composites. Wire cut electric discharge machining holes were produced in a metal matrix composite (10 vol% of SiC in Al6061), which were then investigated to determine the machinability of the material using this process. It was observed that the input factors such as the size of reinforced particles, wire tension and pulse-on time significantly affect diameter error, circularity and surface roughness. Pulse-on time, the interaction between pulse-on time and wire tension contribute to the maximum diameter error. The wire tension is the most significant factor to circularity, which is followed by the interaction between pulse-on time. In particular, wire tension with low and high tensions results in poor circularity. It has been found that there are more surface defects encountered when particle sizes are smaller, and circularity is improved when particles are in a medium size. In addition, the surface defect is reduced as the particles increase the melting resistance of the surface. The higher pulse-on time leads to higher heat and more time to degrade the surface. Therefore, low pulse-on time and wire tension gave better surface finish.